A metal–metal bonding process using metallic copper nanoparticles produced by reduction of copper oxide nanoparticles - Yoshio Kobayashi; Yuki Abe; Takafumi Maeda; Yusuke Yasuda; Toshiaki Morita (Journal of Materials Research and Technology, 2014)
Metal–metal bonding was performed using metallic Cu nanoparticles fabricated from CuO nanoparticles. Colloid solutions of CuO nanoparticles were prepared by the reaction of Cu(NO3)2 and NaOH in aqueous solution at reaction temperatures (TCuOs) of 20, 40, 60 and 80 °C. CuO single crystallites with a size of ca. 10 nm were produced, and they formed leaf-like aggregates. The longitudinal and lateral sizes of the aggregates decreased from 522 to 84 nm and from 406 to 23 nm, respectively, with an increase in TCuO. Colloid solutions of metallic Cu nanoparticles were prepared by reducing the CuO nanoparticles with hydrazine in the presence of cetyltrimethylammonium bromide. The size of the metallic Cu nanoparticles decreased from 92 to 73 nm with increasing TCuO. Metallic copper discs were bonded with the metallic Cu nanoparticles by annealing at 400 °C and 1.2 MPa for 5 min in H2 gas. The shear strength required to separate the bonded discs increased with increasing TCuO. A maximum shear strength of 39.2 MPa was recorded for a TCuO of 80 °C.